Kontrol Diri Siswa dalam Belajar Berdasarkan dari Tahap Perkembangan Masa Remaja - Reni, Reni; Sano, Afrizal (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of self-control for students in the learning process, but there are still gaps related to differences in self-control at various stages of adolescent development. The purpose of this study is to describe the self-control of students who are (1) early adolescence development stage students, (2) mid adolescence development stage students, and (3) test whether there is a significant difference between the two. The research method used is descriptive comparative with a quantitative approach. The study population consisted of UPT students of SMP Negeri 04 Solok Selatan and SMA Negeri 5 Solok Selatan. The research sample was 299 students, selected through stratified random sampling technique. The results showed that students' self-control at the early adolescent and middle adolescent developmental stages was in the moderate category, with a percentage of 51.18% and 68.02% respectively. However, there is no significant difference between students' self-control at the two stages of development (t = 1.647; p > 0.05).